2018
DOI: 10.1007/s12053-018-9746-1
|View full text |Cite
|
Sign up to set email alerts
|

ICT intelligent support solutions toward the reduction of heating demand in cold and mild European climate conditions

Abstract: Adopting intelligent solutions in residential buildings for reducing the HVAC energy demand, especially during the operational stages, is becoming more popular. Information and Communication Technology (ICT) devices are often the backbone of such intelligent solutions, since they can enable an easy and intuitive bidirectional communication between energy systems and users and, at the same time, are able to suggest energy saving procedures. These energy saving procedures are mainly suggested when energy hungry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Cost savings due to implementing smart technologies [6] and [34][35][36][37][38][39] Cost savings due to implementing sustainable approaches [34][35][36][37][38][39] Cost savings due to implementing smart and resilient technologies [30] and [40][41][42][43] Cost savings due to implementing smart technologies and sustainable approaches and maintaining their resilience [6,44] Based on the studies found in Table 1, it can be concluded that most smart buildings are designed to be sustainable. In other words, integrating smart technologies into any building is usually aimed at making the building more convenient, highly efficient, comfortable, and even environmentally friendly.…”
Section: Study Type Referencesmentioning
confidence: 99%
“…Cost savings due to implementing smart technologies [6] and [34][35][36][37][38][39] Cost savings due to implementing sustainable approaches [34][35][36][37][38][39] Cost savings due to implementing smart and resilient technologies [30] and [40][41][42][43] Cost savings due to implementing smart technologies and sustainable approaches and maintaining their resilience [6,44] Based on the studies found in Table 1, it can be concluded that most smart buildings are designed to be sustainable. In other words, integrating smart technologies into any building is usually aimed at making the building more convenient, highly efficient, comfortable, and even environmentally friendly.…”
Section: Study Type Referencesmentioning
confidence: 99%
“…However, only a few studies have assessed the impact of BACS on the energy consumption using detailed building performance simulation models. Reda et al [7] investigated the effect of ICT-driven intelligent solutions for heating and ventilation control in an apartment building through energy simulations in IDA-ICE. They concluded that the energy demand was significantly reduced in buildings with mechanical ventilation, especially in a cold climate.…”
Section: Building Automation Control Systemsmentioning
confidence: 99%
“…As shown by Guillén et al [12], the heating energy saving that can be achieved by moving the set temperature from 20 • C to 19 • C is between 30% and 46% for a nZEB and between 13% and 23% for a traditional dwelling. Reda et al [13] have found that the adoption of information and communication technologies for setting heating setback and indoor setpoint temperatures and for controlling mechanical ventilation can ensure consistent reductions of energy demand.…”
Section: Introductionmentioning
confidence: 99%